(untitled) (ResearchJet Journal of Analysis and Inventions, 2024)
Currently, there are more than two hundred varieties of mulberry for feeding silkworms in our republic, and among them, among the mulberry varieties imported by our breeding scientists, the ones with high productivity and nutritional characteristics are selected according to demand, and by feeding silkworms with fertile mulberry leaves, the biological parameters of larvae and the productivity of cultivated cocoons under the influence of silk gland activity were comparatively studied.